2019
DOI: 10.3390/coatings9020140
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Fretting Wear Behavior of PVD TiCN Coated CuNiAl Blade Bearing in Oil and Artificial Seawater

Abstract: The feasibility of alleviating torsional fretting wear of the blade bearing by preparing PVD TiCN coating was studied. The results show that the friction torque was highly influenced by the wear debris acting as the solid lubricant. The TiCN coating reduced the wear volume by 97.6% and 62.3% in oil and artificial seawater, respectively, which was mainly due to an increase in surface hardness. In oil, the produced sulfates and phosphates prevent seizures between the friction pair and the worn surface was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that coatings produced by physical vapor deposition (PVD) may withstand higher shear stress levels during the rolling phase than coatings produced by chemical vapor deposition (CVD) or thermal spray [20][21][22][23][24][25][26][27]. TiN, TiAlN, TiC, CrN, Cu, and diamond-like carbon (DLC) coatings, produced by PVD [28][29][30][31], have already been studied in rolling-contact fatigue (RCF) tests improving the lifetime of the components [21][22][23][32][33][34]. DLC and carbon nitride (CN) coatings are considered good candidates for its use in rolling components as they provide low friction and high wearing resistance [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that coatings produced by physical vapor deposition (PVD) may withstand higher shear stress levels during the rolling phase than coatings produced by chemical vapor deposition (CVD) or thermal spray [20][21][22][23][24][25][26][27]. TiN, TiAlN, TiC, CrN, Cu, and diamond-like carbon (DLC) coatings, produced by PVD [28][29][30][31], have already been studied in rolling-contact fatigue (RCF) tests improving the lifetime of the components [21][22][23][32][33][34]. DLC and carbon nitride (CN) coatings are considered good candidates for its use in rolling components as they provide low friction and high wearing resistance [35][36][37].…”
Section: Introductionmentioning
confidence: 99%